Determinants of Accounting Information Use with Environmental Uncertainty as Moderation in Food and Beverages MSMEs in Jambi City - Christian Pratenta S; Enggar Arum; Wiralestari (Journal of Economics, Assets, and Evaluation, 2026)
This study examines the determinants of accounting information use among food and beverage MSMEs in Jambi City, with environmental uncertainty as a moderating variable. The use of accounting information is essential for improving decision-making quality and ensuring business sustainability; however, many MSME owners have not yet utilized it optimally. Therefore, this study aims to analyze the effects of business owners’ educational background, business scale, and accounting knowledge on the use of accounting information. A quantitative approach was employed using a survey method. Data were collected through structured questionnaires distributed to 99 MSME owners or managers selected using simple random sampling. The data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) and moderated regression analysis to test both direct and moderating effects. The results show that educational background (β = 0.439; p < 0.001), business scale (β = 0.258; p < 0.001), and accounting knowledge (β = 0.254; p < 0.001) have significant positive effects on accounting information use. Environmental uncertainty significantly moderates the effects of educational background (β = −0.126; p = 0.014) and business scale (β = −0.126; p = 0.034), both in a weakening direction. However, it does not significantly moderate the effect of accounting knowledge (β = −0.036; p = 0.618). The model explains 75.2% of the variance in accounting information use (R² = 0.752). In conclusion, this study highlights that accounting knowledge is the most stable determinant, while environmental uncertainty weakens the influence of other factors. These findings imply that strengthening accounting knowledge through training is a key strategy to improve accounting information use in MSMEs regardless of environmental conditions.